F1 starts to choke off big tobacco - Abd Razak, Dzulkifli (2005)
CONGRATULATIONS Malaysia, for once again successfully hosting the Malaysian leg of the world championship Formula One Grand Prix last month. It was also a race where the Ferrari team led by Michael Schumacher did not clinch a victory. Hopes were high that the German driver would be a leading contender despite failing to finish the season opener in Australia. This is in contrast to last year where he won most of the races. Fernando Alonso dominated the Malaysian Grand Prix to win ahead of a strong drive from Toyota's Jarno Trulli and Williams' Nick Heidfeld. Seventime world champion Schumacher finished a distant seventh. While many sports fans must have felt sorry for the King of Fl, tobacco control advocates have reason to rejoice.